The Model of the Continuum of Teachers? Educational Environment (Cloud ? Silos) - Baron-Polańczyk, Eunika (INSTED: Interdisciplinary Studies in Education & Society, 2016)
The article presents a multi-dimensional model of the continuum of teacher?s activity in the educational environment in the postmodern world implied by the rapid development of ICT (Information and Communication Technology). The designed concept is the result of the analysis of the literature supplemented with the results of the empirical diagnostic/correlative research of a quantitative and qualitative character, specifying information competences of 1160 teachers in the use of ICT methods and tools. The boundary values of the model (the concept-constructs ?cloud? and ?silo?) were determined as well as their referents to six layers including: technology, society, economy, knowledge, culture, philosophy (epistemology, axiology). An attempt was also made to better specify the teachers? activity in the educational environment in athe era of technological and cultural change.